Insulin-like growth factor I receptor blockade enhances chemotherapy and radiation responses and inhibits tumour growth in human gastric cancer xenografts. Issue 5 (14th April 2005) - Min, Y; Adachi, Y; Yamamoto, H; Imsumran, A; Arimura, Y; Endo, T; Hinoda, Y; Lee, C-T; Nadaf, S; Carbone, D P; Imai, K
Abstract : Background and aims: Insulin-like growth factor (IGF) I receptor (IGF-Ir) signalling is required for carcinogenicity and proliferation of many tumours but this pathway has not been studied in detail in gastric cancer. We have previously shown successful therapy for colorectal, pancreatic, and lung cancer using recombinant adenoviruses expressing dominant negative (dn) IGF-Ir. In this study, we sought to better dissect the role of IGF-Ir on progression of gastric cancer and determine whether IGF-Ir targeted adenoviruses represent potentially effective therapeutics for human gastric cancer. Methods: We assessed the effect of IGF-Ir ligands on proliferation and survival in gastric cancer cells in culture. Then, recombinant adenoviruses expressing truncated IGF-Ir (482 and 950 amino acids long, IGF-Ir/dn) that function as dn inhibitors were studied in the treatment of human gastric cancer xenografts. We characterised the effects of IGF-Ir/dn on signalling blockade, growth, apoptosis induction, and in vivo therapeutic efficacy. Results: IGF-Ir signalling promoted tumour growth and survival in gastric cancer. IGF-Ir/dn expression suppressed tumorigenicity both in vitro and in vivo and upregulated stressor induced apoptosis. IGF-Ir/dn blocked Akt-1 activation induced by IGF-I, IGF-II, and des(1-3)IGF-I, but not by insulin. IGF-Ir/dn expression increased radiation and chemotherapy induced apoptosis and the combination of IGF-Ir/dn and chemotherapy was very effective against tumours in mice. In an intraperitoneal model, IGF-Ir/dn therapy also suppressed peritoneal dissemination. Conclusions: IGF-Ir is involved in the regulation of survival and cell growth in human gastric cancer and may be a good molecular therapeutic target. Adenovirus-IGF-Ir/dn may thus have therapeutic use in gastric cancer.